MANAJEMEN PENGELOLAAN KOS-KOSAN DI LINGKUNGAN UINFAS BENGKULU DALAM PERSPEKTIF EKONOMI ISLAM - Nurhayati, Yeni; Supardi Mursalin; Evan Stiawan (Universitas Muhammadiyah Bengkulu, 2023)
The purpose of this research is to understand how to manage boarding houses near UINFAS Bengkulu and to be able to understand how to manage boarding houses from an Islamic economic perspective. This research method uses applied methods in order to obtain accurate information needed by researchers. The results obtained in this study are that most of the boarding houses near UINFAS Bengkulu have carried out management functions, namely organizing and controlling the boarding environment.